Art therapy for Parkinson's disease. (March 2021) - Cucca, Alberto; Di Rocco, Alessandro; Acosta, Ikuko; Beheshti, Mahya; Berberian, Marygrace; Bertisch, Hilary C.; Droby, Amgad; Ettinger, Tom; Hudson, Todd E.; Inglese, Matilde; Jung, Yoon J.; Mania, Daniella F.; et al.
Abstract: Objective: To explore the potential rehabilitative effect of art therapy and its underlying mechanisms in Parkinson's disease (PD). Methods: Observational study of eighteen patients with PD, followed in a prospective, open-label, exploratory trial. Before and after twenty sessions of art therapy, PD patients were assessed with the UPDRS, Pegboard Test, Timed Up and Go Test (TUG), Beck Depression Inventory (BDI), Modified Fatigue Impact Scale and PROMIS-Self-Efficacy, Montreal Cognitive Assessment, Rey-Osterrieth Complex Figure Test (RCFT), Benton Visual Recognition Test (BVRT), Navon Test, Visual Search, and Stop Signal Task. Eye movements were recorded during the BVRT. Resting-state functional MRI (rs-fMRI) was also performed to assess functional connectivity (FC) changes within the dorsal attention (DAN), executive control (ECN), fronto-occipital (FOC), salience (SAL), primary and secondary visual (V1, V2) brain networks. We also tested fourteen age-matched healthy controls at baseline. Results: At baseline, PD patients showed abnormal visual-cognitive functions and eye movements. Analyses of rs-fMRI showed increased functional connectivity within DAN and ECN in patients compared to controls. Following art therapy, performance improved on Navon test, eye tracking, and UPDRS scores. Rs-fMRI analysis revealed significantly increased FC levels in brain regions within V1 and V2 networks. Interpretation: Art therapy improves overall visual-cognitive skills and visual exploration strategies as well as general motor function in patients with PD. The changes in brain connectivity highlight a functional reorganization of visual networks. Highlights: Visuospatial symptoms are highly prevalent but poorly recognized symptoms of Parkinson's Disease. Cumulative disability arising from impaired visuospatial skills may significantly affect patients' quality of life. Effective pharmacological treatments for visuospatial symptoms are lacking. The process of art making relies on sophisticated neurological functions that may be trained to improve visuospatial symptoms in patients with Parkinson's disease. Further studies are warranted to confirm these original findings.